An Enhanced Amperometric Triglyceride Biosensor by Graphene Oxide Nanoparticles - Pundir, Chandra S.; Narwal, Vinay; Kumar, Parveen; Deepa (International Journal of Applied Sciences and Biotechnology, 2025)
An enhanced amperometric triglyceride (TG) biosensor was created by electrodepositing graphene oxide nanoparticles (GrONPs) onto pencil graphite electrode (PGE) and then co-immobilizing enzyme nanoparticles (ENPs) of lipase, glycerol kinase nanoparticles (GKNPs), and glycerol 3-oxidase (GPONPs), onto this modified electrode. Electrochemical impedance spectroscopy (EIS), cyclic voltammetry, and scanning electron microscopy (SEM) were employed to examine the working electrode (ENPs/GrONPs/PGE) at various phases of its creation. At an applied potential of 0.3V, the biosensor showed its best current response within- 2s. The electrode’s ideal pH and temperature were 7.5 and 40˚C, and its linearity was seen for triolein in the concentration range of 0.01 to 60 mM, with a detection limit (LOD) of 0.2 nM. In human serum, the biosensor showed an analytical recovery of 98% for added triolein. The coefficients of variability both within and between batches were 0.048% and 0.05%, respectively. The TG levels in sera as determined by the current biosensor and the conventional enzymic colorimetric technique showed a significant correlation (R2 = 0.99). This biosensor measured the levels of TG in the serum of patients with cardiogenic shock and hyperlipidemia as well as those who appeared to be in apparently healthy condition. The storage stability of electrode revealed only 25% decrease in its initial activity of the electrode, after its regular uses for 240 days of storage in dry condition at 4˚C. Int. J. Appl. Sci. Biotechnol. Vol 13(1): 1-11. Graphical Abstract: Construction of triglyceride biosensor based on LipaseNP/GKNPs/GPONPs/GONS/PGE.